Pengenalan Praktek Kerja Mahasiswa Dalam Melayani Tamu Di Koempoel Bareng Cafe Di Catholic Centre - Furqan, Furqan; Mega Williandani (Cattleya Darmaya Fortuna, 2024)
Student internship programs play a crucial role in higher education by linking theoretical knowledge with practical application in real-world settings. This study investigates the internship experiences of students at Koempoel Bareng Cafe, situated within the Catholic Centre. Emphasizing students' roles in guest service, the research focuses on their interactions with patrons and the practical application of theoretical concepts in customer service contexts. Data collection involved participatory observation and structured interviews with both students and cafe management. Results highlight that these internships enhance students' practical understanding of the service industry while improving their interpersonal skills and professionalism